Primed to perform: Comparing different pre-performance routine interventions to improve accuracy in closed, self-paced motor tasks. (July 2019) - Mesagno, Christopher; Beckmann, Jürgen; Wergin, V. Vanessa; Gröpel, Peter
Abstract: Objectives: Two experimental studies were conducted to test and compare whether different pre-performance routines (i.e., left-hand dynamic handgrip and an extensive routine) can improve (and potentially have a combined effect on) accuracy in closed, self-paced motor tasks. Design/method: Study 1 used a standardised laboratory task to measure motor performance, while Study 2 was a field experiment measuring tenpin bowling accuracy and in-game performance as outcome variables. Both studies consisted of a pretest phase followed by one or two test phases using a group-specific pre-performance routine (PPR), or control, condition. Results: Results of both studies indicated that the inexperienced students (Study 1) and experienced athletes (Study 2) within the intervention groups were more accurate when using the intervention than a control group (not provided an intervention). Using a combined (i.e., left-hand dynamic handgrip and extensive) PPR may not have additive performance effects. Furthermore, using a PPR intervention did not equate to better in-game performance in Study 2. Conclusions: These studies indicate that the element of left-hand dynamic handgrip as a PPR may be comparable to control groups, but further research is needed to determine if it is comparable to extensive PPR interventions that promote concentration on the task for increased performance generally (and under pressure). Highlights: Left-hand dynamic handgrip and extensive routines were compared in two studies. Motor performance was tested on both inexperienced students and skilled athletes. All pre-performance routine groups improved accuracy compared to a control. Combining routines had no greater effect than using the routine in isolation. No differences in groups were apparent for in-game performance in Study 2.